Examining the determinants of agency work: do family friendly practices play a role? - John S. Heywood; William Stanley Siebert; Xiangdong Wei (Institute for the Study of Labor (IZA), 2006)
This paper uses establishment data to estimate the determinants of using agency workers. It contends that those employers with less ability to direct effort of core workers are more likely to use agency workers to meet uncertain labor demand. Family friendly practices are viewed as either increasing or decreasing such ability, depending upon their influence upon absence rates. The empirical results imply that special leave practices reduce firms' ability to direct worker effort, thereby increasing the likelihood of using agency workers. On the other hand, practices linked with flexible working conditions (workplace nurseries, flexitime and job sharing) have the opposite effect. The findings thus distinguish between family friendly practices that make core workers better off without expanding contingent agency jobs, and those that do not.
urn:nbn:de:101:1-20090309158
Keywords: 330